KEBUTUHAN IBU HAMIL AKAN TABLET BESI UNTUK PENCEGAHAN ANEMI - Fitrah Emawati; Yuniar Rosmalina; Susilowati Herman (Persagi, 2000)
THE NEED OF IRON TABLET OF PREGNANT WOMEN TO PREVENT FROM ANEMIA.Background: The prevalence of anemia among pregnant women remain high about 51%. Many studes have been done to reduce prevalence anemia among pregnant women, however the studes do not encourage of the pregnant women to full fill their need of Iron tablet.Objective: To know the knowledge of anemia and its consequence, anemia status and the need of iron tablet of pregnant women who get anemia counseling from midwife and those who did not get counseling.Method: The site of the study was Bogor Municipality. Cohort observation was used in the study. The Subjects were pregnant women of second and third trimester and they were grouped into two groups with and without anemia counseling by midwife during iron tablet administration. The data gathered were the need of iron tablet social economic, knowledge about anemia and its consequence, hemoglobin and hematocrit.Results: we found a significance increase of knowledge about anemia and its consequence in the group of women with anemia counseling, but their need of iron tablet is still low about 20-30 percent in the two groups. There were 52 percent women with counseling group consuming the entire tablet given from midwife. However, anemia was remaining high 46,2 percent among pregnant women with counseling group.Conclusions: The percentage of anemia after four month anemia counseling is high since the need of iron tablet of pregnant women is low.Key Words: pregnant women, iron tablet anemia